Decisional Profile on Competing Volleyball Athletes From Autonomous University of Chihuahua (Uach): Gender Comparison - Juan Cristobal Barron Lujan; Silvia Isela Ramírez Enríquez; Héctor Luis Medina Lopez; Gilberto Santos Sambrano; Leopoldo Refugio Lopez Baca; Gabriel Gastelum Cuadras (European Scientific Journal, ESJ, 2019)
Sports psychology considers the athlete as an individual capable of processing information and making their own decisions which reflects in the results obtained as a team in a competition within the sports environment. This paper focuses on comparing the competing decisional profile on the sports performance of volleyball players at the Autonomous University of Chihuahua and also determines gender differences. For this, a descriptive, comparative investigation was carried out, where 24 representative athletes of the university participated in this discipline. Here, the questionnaire of Decision Style in the Sport of Ruiz and Graupera (2005) was applied to measure aspects of decision making in sports. Among the most relevant aspects is the commitment to their training. It combines not only the concern for the adversary, for knowing their customs and their concerns in the competition, but clearly emphasizes the importance of relying on the coach's tactical plan and following his instructions. The results analyzed with the Mann-Whitney U test show that there are no differences in the decision profile between genders; however, it was determined that the men presented themselves to present perceived decision-making competence and commitment to decisionmaking than women, plus, they face less anxiety and stress when deciding. Therefore, it is concluded that the decision profile may be related to the competitive experience, since the men of the present study have shown better sports performance in previous meetings than women.